Method for preparing high-density and low-resistivity titanium nitride film through magnetron sputtering

By using magnetron sputtering technology in an ultra-high vacuum and low-temperature environment, the process parameters are optimized to prepare titanium nitride films, which solves the problems of high impurity content and high deposition temperature of titanium nitride films in the existing technology, and achieves high precision. Thin film preparation with high density and low resistivity is suitable for the back-end process of integrated circuits.

CN119332206APending Publication Date: 2025-01-21NANJING UNIV

Patent Information

Application Number
CN202411437144.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In the prior art, the impurity content of the titanium nitride film is high and the deposition temperature is high, which affects its conductivity and applicability, especially in the back-end process of integrated circuits.

Method used

Magnetron sputtering technology in ultra-high vacuum and low-temperature environment is used to prepare high-density, low-resistivity titanium nitride films by optimizing process parameters such as sputtering power, air pressure, substrate temperature and target-base distance.

Benefits of technology

It achieves the growth of high-density, low-resistivity titanium nitride films at lower temperatures, reduces impurity content and resistivity, is compatible with integrated circuit back-end processes, and improves the application prospects of the film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119332206A_ABST
    Figure CN119332206A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a titanium nitride film with high density and low resistivity through magnetron sputtering. A semiconductor wafer is adopted as a substrate, and the substrate is conveyed into a magnetron sputtering reaction chamber with an ultrahigh vacuum background through an ultrahigh vacuum interconnection pipeline; a titanium nitride compound is adopted as a target material, and argon is introduced for non-chemical reaction magnetron sputtering after a sample table reaches the required film deposition temperature; after sputtering is completed, gas introduction is stopped, and the molecular pump recovers the vacuum degree in the cavity to ultrahigh vacuum as soon as possible; cooling the heating table to room temperature and then taking out the sample; the low-resistance titanium nitride thin film is finally prepared by adopting specially selected parameters such as sputtering power, substrate temperature, target-substrate distance and sputtering air pressure, and after technological parameters are stabilized, the thickness of the thin film is controlled by controlling sputtering time; the method is high in feasibility, the ultrathin conductive film with low resistivity, good uniformity and surface flatness can be prepared, and the method has wide and important application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a titanium nitride film, in particular to a method for preparing a high-density, low-resistivity titanium nitride film by magnetron sputtering. Background Art

[0002] The structure of the fourth group transition metal nitride is usually a mixture of metallic bonds and covalent bonds, and has the characteristics of metal crystals and covalent crystals: high melting point, high hardness, excellent thermal conductivity, chemical inertness and electrical conductivity. This type of film can be widely used in various fields, among which titanium nitride (TiN x ) film. Titanium nitride crystals belong to the cubic system, have a face-centered cubic structure, and have a lattice constant of 0.4239nm. Titanium nitride film can be used as a wear-resistant hard film and is widely used in various cutting tools and mechanical parts, and can also be used as a decorative film in various decoration industries. In the field of integrated circuits, it can be used as a diffusion barrier between Cu and Si in circuit chips to effectively prevent the diffusion of Cu.

[0003] At present, the commonly used preparation processes for TiN films include sputtering deposition, chemical vapor deposition, pulsed laser deposition, etc. However, in these methods, due to the environmental cleanliness and vacuum limitations during the sample transfer and preparation process, there are high impurity contents at the initial interface and inside the film. These impurities will cause the quality of TiN crystallization to deteriorate, thereby affecting its conductivity. Sputtering deposition generally uses Ti metal target atoms to sputter and react with nitrogen to form titanium nitride, but the reaction is not sufficient due to insufficient nitrogen activity. In addition, these preparation methods generally require higher deposition temperatures to obtain TiN films with lower resistivity, but high-temperature processes are not compatible with integrated circuit back-end processes. Therefore, from the perspective of practical applications, the deposition technology and processes of the existing technology must be improved and perfected. Summary of the invention

[0004] Purpose of the invention: The purpose of the present invention is to provide a method for preparing high-density, low-resistivity titanium nitride film by magnetron sputtering in an ultra-high vacuum and low-temperature environment, to solve the problems of high impurity content and high deposition temperature in the film in the prior art, to lay the foundation for its application in the back-end process of integrated circuits and to provide a technical solution.

[0005] Technical solution: The method for preparing high-density, low-resistivity titanium nitride film by magnetron sputtering of the present invention comprises the following steps:

[0006] (1) Preprocessing a semiconductor wafer to obtain a substrate substrate;

[0007] (2) Under vacuum conditions, the substrate is transferred to the magnetron sputtering reaction chamber of the ultra-high vacuum magnetron sputtering equipment through a transfer pipeline. The vacuum degree of the transfer pipeline is 10 -10Below Torr level;

[0008] (3) extracting the background vacuum to degas the surface of the substrate, using the titanium nitride compound as the target, heating, introducing argon gas, adjusting the power, and performing pre-sputtering;

[0009] (4) adjusting the target-substrate distance, sputtering power, and sputtering gas pressure, and performing DC magnetron sputtering on the substrate to grow a thin film;

[0010] (5) After the sputtering is completed, stop introducing gas, turn on the high vacuum gauge to restore ultra-high vacuum in the magnetron sputtering reaction chamber, and take out the sample after the heating table cools to room temperature.

[0011] Among them, in step (1), the pretreatment is to use organic ultrasonic cleaning, the steps are two acetone ultrasonic cleanings for 5 minutes, followed by 5 minutes of isopropanol ultrasonic cleaning; after completion, it is fully washed with deionized water and finally blown dry with a nitrogen gun.

[0012] Wherein, in step (1), the semiconductor wafer is a single-sided or double-sided polished single crystal silicon wafer or silicon oxide wafer.

[0013] Wherein, in step (3), the target material is a titanium nitride compound with a purity of 99.999%, a diameter of 50 mm and a thickness of 5 mm.

[0014] Wherein, in step (3), the pre-sputtering has a power of 50W-80W and a duration of 15min-45min; further, preferably, the power is 80W and the duration is 15min.

[0015] Wherein, in step (4), the background vacuum degree is 4×10 -10 Torr; the flow rate of the introduced argon gas is 20sccm-50sccm, preferably 20sccm, the vacuum degree in the vacuum chamber is maintained at 2-3mTorr, preferably 2mTorr, and the purity of the introduced argon gas is 99.999%.

[0016] Wherein, in step (4), the substrate temperature of magnetron sputtering is in the range of 375-425°C, the sputtering power is in the range of 45-60W, the operating voltage is 250-300V, the target-substrate distance is in the range of 135-150mm, and the time for growing the thin film is 2 to 20 minutes.

[0017] The present invention also discloses a TiN film prepared by the above method, which has a low impurity level, a stable Ti to N stoichiometric ratio of 1-1.05, an O content of less than 3%, a C content of less than 1%, a surface root mean square roughness of less than 1nm, and a density of about 5.7g / cm calculated by XRR. 3The resistivity of the 26.07nm thick film is less than 74μohm·cm; the resistivity of the 12.5nm thick film is less than 85μohm·cm; the resistivity of the 3nm thick TiN film is less than 200μohm·cm.

[0018] Principle of the invention: The present invention provides a method for preparing high-density, low-resistivity titanium nitride film by magnetron sputtering. By optimizing relevant process parameters, growth can be achieved under ultra-high vacuum and relatively low temperature conditions. After theoretical investigation and experimental demonstration, the key factors restricting the resistivity of Sputter TiN film are sputtering power, sputtering gas pressure, substrate temperature and target-substrate distance. Increasing power and temperature and lowering gas pressure can make the sputtered atoms have greater kinetic energy when they reach the substrate, and the atomic migration and rearrangement capabilities become stronger, which is conducive to crystal crystallization. However, such an optimization direction also has a critical point. Excessive surface migration energy may lead to an excessively fast crystallization rate, causing defects inside the grains, which in turn reduces the crystal quality of the film. At the same time, the increase in surface roughness will also limit its application prospects.

[0019] The overall process flow of this method is relatively simple, the film resistivity is low, the uniformity and flatness are good, and the impurity level is low. And it is transferred to various characterization equipment through a vacuum transfer device, which maintains the cleanliness of the sample surface at the atomic level, and minimizes the interference of impurities during the processing and transfer process, and has a relatively broad application prospect. Especially in the back-end process of integrated circuits, the TiN nanocrystalline structure prepared by this invention has no vertical grain boundary pathways. The traditional reactive sputtering grown TiN has high migration energy of deposited particles, low lateral mobility, and tends to grow vertically, which can effectively improve the film's ability to block copper diffusion. It has great advantages in the application of interconnect diffusion barrier layers.

[0020] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The preparation process is simple, the energy consumption is low, and the growth can be achieved at a relatively low temperature. The current technology, such as pulsed laser deposition, may only be able to obtain a TiN film with good density and low resistivity when the bottom temperature reaches above 700 degrees Celsius; while the present invention reduces the deposition temperature to below 400 degrees Celsius, which is expected to be compatible with the back-end interconnection process of integrated circuits; (2) The obtained conductive film has good uniformity and flatness, and the impurity level is extremely low, which can be applied to the interconnection process of advanced integrated circuit processes. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the structure diagram of the ultra-high vacuum magnetron sputtering system;

[0022] Figure 2 is a schematic diagram of the growth chamber;

[0023] Figure 3This is the AFM surface morphology image obtained in Example 1;

[0024] Figure 4 This is a graph of the XRR test results obtained in Example 1;

[0025] Figure 5 The XPS test results obtained in Example 1 are shown in Figure 1, where (a) is the full XPS spectrum, and (b)-(e) are the detailed spectra of Ti 2p, N1s, O 1s, and C 1s, respectively;

[0026] Figure 6 The XRD results of TiN films with different thicknesses grown according to Example 1;

[0027] Figure 7 Figures a, b, and c are Raman spectrum test result diagrams of Examples 1, 4, and 5, respectively;

[0028] Figure 8 This is the TEM test result diagram obtained in Example 1. DETAILED DESCRIPTION

[0029] The technical scheme of the present invention is further described below in conjunction with the examples. The test materials used in the examples can all be purchased through conventional channels.

[0030] Example 1

[0031] The method for preparing a high-density, low-resistivity titanium nitride film by magnetron sputtering in an ultra-high vacuum and low-temperature environment of the present invention comprises the following steps:

[0032] (1) A single-sided polished 2-inch silicon oxide substrate was used as the substrate for organic ultrasonic cleaning. The prepared sample was placed in the pipeline sample chamber with the front side facing up. A TiN compound target with a purity of 99.99% was installed at the ultra-high vacuum magnetron sputtering strong magnetic target head. The target material had a diameter of 50 mm and a thickness of 5 mm.

[0033] (2) Turn on the magnetron sputtering equipment, start the mechanical pump and the molecular pump to extract the vacuum, and reach the background vacuum of 4×10-10Torr. Then manually raise the gate valve, use the transmission magnetic rod to send in the sample and the protective cover, raise the Z axis, send out the transmission rod, and close the gate valve. Raise the temperature of the substrate table to 400℃ and maintain it for 15 minutes.

[0034] (3) Turn on the DC sputtering power supply, cover the substrate surface with a baffle, and turn off the high vacuum gauge. Pass a higher flow rate of Ar gas, set a higher sputtering power, and perform pre-sputtering for 20 minutes after ignition to clean impurities on the target surface.

[0035] (4) Adjust the target-substrate distance to 150 mm, the sputtering power to 60 W, the sputtering pressure in the chamber to 2 mTorr (Ar gas flow rate to 20 sccm), open the baffle covering the substrate surface, perform DC magnetron sputtering, keep the temperature constant, and fix the substrate position.

[0036] (5) After the film has grown for 2-20 minutes, stop the introduction of Ar gas and heating, and turn on the high vacuum gauge after 5 minutes. When the temperature of the heating table cools down to below 150 degrees Celsius, take out the sample, and the pipeline manipulator takes the sample and uses a trolley to transport it to the relevant test characterization equipment through the vacuum pipeline.

[0037] The resistivity of the 26.07nm thick TiN film (sputtering time 20min) prepared using the process parameters is less than 74μohm·cm; the resistivity of the 12.5nm thick TiN film (sputtering time 9min) is less than 85μohm·cm; the resistivity of the 3nm thick TiN film (sputtering time about 2min30s) is less than 200μohm·cm.

[0038] Figure 3 , Figure 4 The AFM surface morphology test image and XRR test result obtained in Example 1 are shown respectively. By fitting and analyzing the relevant experimental data, the surface root mean square roughness is less than 0.9nm and the film density is about 5.7g / cm 3 , showing higher density, better than most reports in the literature.

[0039] XPS test (such as Figure 5 The results show that the impurity level of the film is low, the stoichiometric ratio of Ti to N is stable at 1-1.05, the O content is less than 3%, and the C content is less than 1%. The peak intensity of TiON is significantly higher than that of TiO2, indicating that oxygen in the film mainly forms TiO x N y The formed TiO x N y When the oxygen content is low, the rock salt structure of TiN can be maintained, and its properties are closer to those of TiN, and its conductivity is better than that of TiO2.

[0040] Figure 7 In the Raman spectra of Examples 1, 4, and 5, by analyzing the TO and TA peaks, it can be seen that with the optimization of the process, the film point defects are getting smaller and smaller, and the crystal quality is improved. Figure 6 XRD and Figure 8 TEM test results show that the TiN crystals prepared by the joint reaction have random orientation and are typical nanocrystalline structures. Similarly, the TiN film obtained by the same preparation method with only the substrate replaced by a single crystal silicon wafer has similar properties.

[0041] Example 2

[0042] (1) A single-sided polished 2-inch silicon oxide substrate was used as the substrate for organic ultrasonic cleaning. The prepared sample was placed in the pipeline sample chamber with the front side facing up. A TiN compound target with a purity of 99.99% was installed at the ultra-high vacuum magnetron sputtering strong magnetic target head. The target material had a diameter of 50 mm and a thickness of 5 mm.

[0043] (2) Turn on the magnetron sputtering equipment, start the mechanical pump and molecular pump to extract the vacuum, and reach the background vacuum of 4×10 -10 Torr. Then manually raise the gate valve, use the transmission magnetic rod to send in the sample and protective cover in turn, raise the Z axis, send out the transmission rod, and close the gate valve. Heat the substrate table to 400℃ and keep it for 15 minutes.

[0044] (3) Turn on the DC sputtering power supply, cover the substrate surface with a baffle, and turn off the high vacuum gauge. Pass a higher flow rate of Ar gas, set a higher sputtering power, and perform pre-sputtering for 20 minutes after ignition to clean impurities on the target surface.

[0045] (4) Adjust the target-substrate distance to 150 mm, the sputtering power to 60 W, the sputtering gas pressure in the chamber to 2 mTorr (Ar gas flow rate 16 sccm, N2 gas flow rate 5 sccm), open the baffle covering the substrate surface, perform DC magnetron sputtering, keep the temperature unchanged, and fix the substrate position.

[0046] (5) After 20 minutes of film growth, stop introducing gas and heating at the same time, and turn on the high vacuum gauge after 5 minutes. When the temperature of the heating table drops below 150 degrees Celsius, take out the sample, and the pipeline manipulator takes the sample and uses a trolley to transport it to the relevant test characterization equipment through the vacuum pipeline.

[0047] It was measured that the thickness of the TiN film prepared in Example 2 was about 25nm and the resistivity was about 3500μohm·cm. Combined with the specific experimental phenomena and existing literature, in the non-reactive sputtering of TiN, the addition of N2 will deteriorate the crystallinity, which will lead to a sharp increase in resistivity. N2 should not be introduced in subsequent process exploration. Finally, the XPS results show that the film contains a high content of oxygen elements. Analysis shows that its source is mainly adsorbed impurities on the surface of the target material. The pre-sputtering time should be extended in the future.

[0048] Example 3

[0049] (1) A single-sided polished 2-inch silicon oxide substrate was used as the substrate for organic ultrasonic cleaning. The prepared sample was placed in the pipeline sample chamber with the front side facing up. A TiN compound target with a purity of 99.99% was installed at the ultra-high vacuum magnetron sputtering strong magnetic target head. The target material had a diameter of 50 mm and a thickness of 5 mm.

[0050] (2) Turn on the magnetron sputtering equipment, start the mechanical pump and molecular pump to extract the vacuum, and reach the background vacuum of 4×10 -10 Torr. Then manually raise the gate valve, use the transmission magnetic rod to send in the sample and protective cover in turn, raise the Z axis, send out the transmission rod, and close the gate valve. Heat the substrate table to 400℃ and keep it for 15 minutes.

[0051] (3) Turn on the DC sputtering power supply, cover the substrate surface with a baffle, and turn off the high vacuum gauge. Pass a higher flow rate of Ar gas, set a higher sputtering power, and perform pre-sputtering for 20 minutes after ignition to clean impurities on the target surface.

[0052] (4) Adjust the target-substrate distance to 150 mm, the sputtering power to 70 W, the sputtering pressure in the chamber to 2 mTorr (Ar gas flow rate to 20 sccm), open the baffle covering the substrate surface, perform DC magnetron sputtering, keep the temperature constant, and fix the substrate position.

[0053] (5) After 20 minutes of film growth, stop the introduction of Ar gas and heating at the same time, and turn on the high vacuum gauge after 5 minutes. When the temperature of the heating table drops below 150 degrees Celsius, take out the sample, and the pipeline manipulator takes the sample and uses a trolley to transport it to the relevant test characterization equipment through the vacuum pipeline.

[0054] Example 4

[0055] (1) A single-sided polished 2-inch silicon oxide substrate was used as the substrate for organic ultrasonic cleaning. The prepared sample was placed in the pipeline sample chamber with the front side facing up. A TiN compound target with a purity of 99.99% was installed at the ultra-high vacuum magnetron sputtering strong magnetic target head. The target material had a diameter of 50 mm and a thickness of 5 mm.

[0056] (2) Turn on the magnetron sputtering equipment, start the mechanical pump and molecular pump to extract the vacuum, and reach the background vacuum of 4×10 -10 Torr. Then manually raise the gate valve, use the transmission magnetic rod to send in the sample and protective cover in turn, raise the Z axis, send out the transmission rod, and close the gate valve. Heat the substrate table to 300℃ and maintain it for 15 minutes.

[0057] (3) Turn on the DC sputtering power supply, cover the substrate surface with a baffle, and turn off the high vacuum gauge. Pass a higher flow rate of Ar gas, set a higher sputtering power, and perform pre-sputtering for 40 minutes after ignition to clean impurities on the target surface.

[0058] (4) Adjust the target-substrate distance to 150 mm, the sputtering power to 60 W, the sputtering pressure in the chamber to 2 mTorr (Ar gas flow rate to 20 sccm), open the baffle covering the substrate surface, perform DC magnetron sputtering, keep the temperature constant, and fix the substrate position.

[0059] (5) After 20 minutes of film growth, stop the introduction of Ar gas and heating at the same time, and turn on the high vacuum gauge after 5 minutes. When the temperature of the heating table drops below 150 degrees Celsius, take out the sample, and the pipeline manipulator takes the sample and uses a trolley to transport it to the relevant test characterization equipment through the vacuum pipeline.

[0060] Example 5

[0061] (1) A single-sided polished 2-inch silicon oxide substrate was used as the substrate for organic ultrasonic cleaning. The prepared sample was placed in the pipeline sample chamber with the front side facing up. A TiN compound target with a purity of 99.99% was installed at the ultra-high vacuum magnetron sputtering strong magnetic target head. The target material had a diameter of 50 mm and a thickness of 5 mm.

[0062] (2) Turn on the magnetron sputtering equipment, start the mechanical pump and molecular pump to extract the vacuum, and reach the background vacuum of 4E - 10 Torr. Then manually raise the gate valve, use the transmission magnetic rod to send in the sample and protective cover in turn, raise the Z axis, send out the transmission rod, and close the gate valve. Heat the substrate table to 400℃ and keep it for 15 minutes.

[0063] (3) Turn on the DC sputtering power supply, cover the substrate surface with a baffle, and turn off the high vacuum gauge. Pass a higher flow rate of Ar gas, set a higher sputtering power, and perform pre-sputtering for 40 minutes after ignition to clean impurities on the target surface;

[0064] (4) Adjust the target-substrate distance to 120 mm, the sputtering power to 60 W, the sputtering pressure in the chamber to 2 mTorr (Ar gas flow rate to 20 sccm), open the baffle covering the substrate surface, perform DC magnetron sputtering, keep the temperature constant, and fix the substrate position.

[0065] (5) After 20 minutes of film growth, stop the introduction of Ar gas and heating at the same time, and turn on the high vacuum gauge after 5 minutes. When the temperature of the heating table drops below 150 degrees Celsius, take out the sample, and the pipeline manipulator takes the sample and uses a trolley to transport it to the relevant test characterization equipment through the vacuum pipeline.

[0066] Embodiments 3-5 adopt an orthogonal experimental method to change the sputtering power, sputtering pressure, substrate temperature and target-substrate distance. According to measurement, the thickness of the TiN film prepared in embodiment 3 is about 28nm, and the resistivity is about 280μohm·cm; the thickness of the TiN film prepared in embodiment 4 is about 25nm, and the resistivity is about 350μohm·cm; the thickness of the TiN film prepared in embodiment 5 is about 27nm, and the resistivity is about 120μohm·cm, which are significantly higher than the sample obtained in embodiment 1. After theoretical investigation and experimental demonstration, the key factors restricting the resistivity of Sputter TiN film are sputtering power, sputtering pressure, substrate temperature and target-substrate distance. Increasing power and temperature and reducing pressure can make the sputtered atoms have greater kinetic energy when they reach the substrate, and the atomic migration and rearrangement ability become stronger, which is conducive to crystal crystallization. However, such an optimization direction also has a critical point. Excessive surface migration energy may lead to too fast a crystallization rate, causing defects inside the grains, but reducing the crystal quality of the film. At the same time, the increase in surface roughness will also limit its application prospects.

Claims

1. A method for preparing a high-density, low-resistivity titanium nitride film by magnetron sputtering, characterized in that: The following steps are involved: (1) Preprocessing a semiconductor wafer to obtain a substrate substrate; (2) Under vacuum conditions, the substrate is transferred to the magnetron sputtering reaction chamber of the ultra-high vacuum magnetron sputtering equipment through a transfer pipeline. The vacuum degree of the transfer pipeline is 10 -10 Below Torr level; (3) extracting the background vacuum to degas the surface of the substrate, selecting the target material, heating, introducing argon gas, adjusting the power, and performing pre-sputtering; (4) adjusting the target-substrate distance, sputtering power, and sputtering gas pressure, and performing DC magnetron sputtering on the substrate to grow a thin film; (5) After the sputtering is completed, stop introducing gas, turn on the high vacuum gauge to restore ultra-high vacuum in the magnetron sputtering reaction chamber, and take out the sample after the heating table cools to room temperature.

2. The method according to claim 1, characterized in that In step (1), the pretreatment is to use organic ultrasonic cleaning, the steps are two acetone ultrasonic cleanings for 5 minutes, followed by 5 minutes of isopropanol ultrasonic cleaning; after completion, it is fully washed with deionized water and finally blown dry with a nitrogen gun.

3. The method according to claim 1, characterized in that In step (1), the semiconductor wafer is a single-sided or double-sided polished single crystal silicon wafer or silicon oxide wafer.

4. The method according to claim 1, characterized in that: In step (3), the target material is a titanium nitride compound with a purity of 99.999%.

5. The method according to claim 1, characterized in that In step (3), the pre-sputtering has a power of 50W-80W and a duration of 15min-45min.

6. The method according to claim 1, characterized in that In step (4), the background vacuum is 4×10 -10 Torr; the flow rate of the introduced argon gas is 20sccm-50sccm, the vacuum degree in the vacuum chamber is maintained at 2mTorr-3mTorr, and the purity of the introduced argon gas is 99.999%.

7. The method according to claim 1, characterized in that In step (4), the substrate temperature of magnetron sputtering is in the range of 375-425° C., the sputtering power is in the range of 45-60 W, the operating voltage is 250-300 V, and the target-substrate distance is in the range of 135-150 mm.

8. The method according to claim 1, characterized in that In step (4), the time for growing the thin film is 2 to 20 minutes.

Citation Information

Patent Citations

  • Preparation method for high-quality TiN thin film

    CN106884142A

  • Titanium nitride film with highly preferred orientation (100) and growing on silicon substrate, and preparation method thereof

    CN107022744A

  • Method for preparing low-resistance titanium nitride film through low-temperature magnetron sputtering

    CN107058962A

  • Method for preparing titanium nitride superconductive film on silicon substrate by using magnetron sputtering method

    CN108588653A

  • Deoisition method of titanium nitride

    KR1019980021727A

Cited By

  • Preferred orientation titanium nitride functional film as well as preparation method and application thereof

    CN122061119A

  • Method for preparing single crystal TiN film based on pulse direct current magnetron sputtering and film

    CN122061248A